The Effect of Yoga Intervention on Reducing Anxiety Levels in Pregnant Women: A Literature Review - Yeni Septia Ningsi; Nur Hidayatul Ainiyah (PT Pubsains Nur Cendekia, 2025)
Background: Pregnancy is a period of significant physiological and psychological adaptation in a woman's life. In addition to hormonal and physical changes, many pregnant women experience emotional fluctuations, including increased levels of anxiety. Objective: This study aims to evaluate the effect of yoga on anxiety levels in pregnant women based on findings from previous studies. Methods: This literature review was conducted in July 2025. The literature search was performed using four major electronic databases: Scopus (33 articles), PubMed (9 articles), and Google Scholar (10 articles). The keywords used were